Nitrogen deposition to lakes in national parks of the western Great Lakes region: Isotopic signatures, watershed retention, and algal shifts. Issue 3 (19th March 2016) - Hobbs, William O.; Lafrancois, Brenda Moraska; Stottlemyer, Robert; Toczydlowski, David; Engstrom, Daniel R.; Edlund, Mark B.; Almendinger, James E.; Strock, Kristin E.; VanderMeulen, David; Elias, Joan E.; Saros, Jasmine E.
Abstract: Atmospheric deposition is a primary source of reactive nitrogen (Nr) to undisturbed watersheds of the Great Lakes region of the U.S., raising concerns over whether enhanced delivery over recent decades has affected lake ecosystems. The National Atmospheric Deposition Program (NADP) has been measuring Nr deposition in this region for over 35 years. Here we explore the relationships among NADP‐measured Nr deposition, nitrogen stable isotopes (δ 15 N) in lake sediments, and the response of algal communities in 28 lakes situated in national parks of the western Great Lakes region of the U.S. We find that 36% of the lakes preserve a sediment δ 15 N record that is statistically correlated with some form of Nr deposition (total dissolved inorganic N, nitrate, or ammonium). Furthermore, measured long‐term (since 1982) nitrogen biogeochemistry and inferred critical nitrogen loads suggest that watershed nitrogen retention and climate strongly affect whether sediment δ 15 N is related to Nr deposition in lake sediment records. Measurements of algal change over the last ~ 150 years suggest that Nr deposition, in‐lake nutrient cycling, and watershed inputs are important factors affecting diatom community composition, in addition to direct climatic effects on lake physical limnology. The findings suggest that bulk sediment δ 15 N does reflect Nr deposition in some instances. In addition, this study highlights the interactive effects of Nr deposition and climate variability. Key Points: Lake sediments can record trends in the atmospheric deposition of reactive nitrogen (Nr) Watershed N retention affects whether lake sediment δ 15 N is related to Nr deposition The interactive effects of climate and nutrients force changes in algal communities